From resentment to excitement – Australasian students’ perception towards a sales career - Handley, B.; Shanka, Tekle; Rabbanee, Fazlul (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to explore Australasian students’ current perception towards a sales career. Design/methodology/approach: Data were collected through a self-administered survey from 431 students enrolled in a Sales Management unit in a large Australian university and its Asian campuses. Findings: The study reveals a four-factor solution with factors labeled as “exciting,” “deceptive,” “taxing,” and “challenging,” with “exciting” being the only factor to significantly predict likelihood of pursuing a sales career. Although no differences of perception were found between males and females, Asian students were found to perceive sales career as more exciting, innovative and fun than Australian students. Research limitations/implications: Although significant difference was noted between Australian and Asian students’ perceptions towards sales as an exciting career, it is prudent to interpret and generalize the finding with caution as Asia is the largest continent with different cultures, religions and races. Practical implications: The four factors that were found to influence students’ perception towards a sales career are novel, psychometrically sound, and are pertinent for businesses conducting graduate recruitment. This study indicates how sales education at university level assist in changing students’ views towards a sales career from negative to positive. Originality/value: While previous research has reported negative perceptions about sales as a career, this study reveals that students consider sales to be an “exciting” career.